Bench-to-bedside Strategies for Osteoporotic Fractures : A Systematic Literature Review - Bakti Rakha Astagina, yodha (International Journal Labs, 2025)
Osteoporotic fractures represent a significant global health burden, particularly among aging populations. The purpose of this study is bench-to-bedside strategies for preventing and treating osteoporotic fractures through systematics reviews from various sources. A systematic review on clinical interventions for preventing and treating osteoporotic fractures typically employs a rigorous methodology to synthesize and analyze existing research. The process begins with a comprehensive literature search across multiple databases, including PubMed, Cochrane Library, EMBASE, and Web of Science. Bench-to-bedside strategies for osteoporotic fractures have resulted in substantial advances in the understanding, prevention, and management of this condition. The integration of basic scientific discoveries with clinical applications has resulted in better diagnostic tools, more effective therapies, and improved treatment models. These novel strategies represent a multidisciplinary approach to tackling osteoporotic fractures. By combining advanced diagnostics, targeted therapeutics, and personalized interventions, the bench-to-bedside pipeline aims to significantly reduce fracture incidence and improve patient outcomes.